Mechanical Characterization of Individual Needles in Microneedle Arrays: Factors Affecting Compression Test Results - Yusuke Tsuboko; Hideyuki Sakoda; Yoshihiro Okamoto; Yusuke Nomura; Eiichi Yamamoto (MDPI AG, 2024)
Background: This study aims to investigate the impact of test conditions on the results of the compression testing of microneedle arrays (MNAs). Methods: Uniaxial compression tests were conducted on polyglycolic acid-fabricated biodegradable MNAs. Load-displacement curves were obtained for varying conditions, including the number of microneedles (MNs) compressed simultaneously, compression speeds, and compression angles. Subsequently, the buckling load and stiffness were calculated, and the MN deformation during compression was observed. Results: The buckling load and stiffness per MN decreased significantly with a simultaneous increase in compressed MNs. The mean buckling load and stiffness of 52 MNs in single-needle compression tests were 0.211 ± 0.008 N and 13.9 ± 1.3 N/mm, respectively, with no variation among the three MNAs. However, a significant difference in buckling load and stiffness was observed among the MNs within the MNAs. Additionally, buckling loads and stiffnesses were significantly lower in certain MNs at the same location in different MNAs. Buckling load and stiffness decreased significantly during inclined compression compared to during vertical compression. While the tests evaluate the mechanical properties of MNAs, test results may vary depending on test conditions. Conclusions: Compression testing of the individual MNs comprising an MNA helps evaluate the mechanical properties of MNs and ensure the quality of MNAs.